2020
DOI: 10.31234/osf.io/3xdg8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Initial Evidence that Parent-Child Conversations About Race Reduce Racial Biases Among White U.S. Children

Abstract: Despite the fact that having conversations about race has been recommended as a way to curb children’s racial biases, no prior work has directly tested the impact of parents having these (racial socialization) conversations with their children. Most White American parents avoid talking about race and racism with their children, which seems to be due, in part, to White parents’ fear that increasing their children’s awareness and acknowledgement of race could lead to increased racial biases. With the current wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 1 publication
1
19
0
1
Order By: Relevance
“…Within the context of talking about illness parents often convey information to their children about the causes of illnesses that are consistent with their own beliefs and the larger culture (Hernandez et al, 2020). Therefore, parental responses to questions might shape children's thinking and behavior (Perry et al, 2020).…”
mentioning
confidence: 99%
“…Within the context of talking about illness parents often convey information to their children about the causes of illnesses that are consistent with their own beliefs and the larger culture (Hernandez et al, 2020). Therefore, parental responses to questions might shape children's thinking and behavior (Perry et al, 2020).…”
mentioning
confidence: 99%
“…Specifically, we observed a significant decrease in anti-Black bias from pretest to posttest among children who discussed with their parents brief animated stories about White children displaying racial biases toward Black children. But, importantly, we also found that these effects occurred, irrespective of whether the parent showed nonverbal signals indicative of anxiety, tenseness, or physiological arousal (Perry et al, 2020). In fact, this new evidence suggests that, under certain circumstances, parents’ tenseness and physiological arousal may actually be associated with even greater decreases in children’s racial biases.…”
Section: Advantages Of Explicit Racial-socialization Conversationsmentioning
confidence: 69%
“…Preliminary results suggest the method facilitated color-conscious conversations, such that parents mentioned race and pointed out that prejudice had occurred in the vignettes at a higher rate than previous self-report and lab studies have shown. Furthermore, both parents and children showed decreased pro-White/anti-Black implicit attitudes after the conversation (Perry et al, 2021). Despite the aforementioned barriers, we believe that interventions at the family level have the potential to be high impact, as two generations can be targeted at once, and families can potentially encourage children to be critical of the colorblind, White-centric messages they receive at school or in other contexts.…”
Section: Child Development and The Pursuit Of Equalitymentioning
confidence: 96%